Campur Kode pada Komunikasi Lisan antar Para Pelaku Percakapan di Pasar Grosir Setono Pekalongan - Ida Ayu Panuntun (JURNAL LITBANG KOTA PEKALONGAN, 2021)
Communication is a media in transferring idea between speaker and hearer. Oral communication often used by the speaker and hearer in achieving the aim of communication. Most of Indonesian people, included Pekalongan people are bilingual. They use Javanese language as their daily language. However, as Indonesian people, they also master and use Indonesian language in their conversation. Sometimes, they often mix Javanese and Indonesian in their conversation. It also happened in the conversation between seller and buyer in Pasar Grosir Setono Pekalongan. Most of the sellers came from Pekalongan. It means that in providing services for the buyer, sometimes the sellers combined Indonesian and Javanese language. They often inserted another language in their conversation. The aim of this research was to describe the form of code mixing used between seller and buyer in Pasar Grosir Setono Pekalongan. The research design used in this research was descriptive qualitative. The instrument was observation sheet. There are 15 sellers and 17 buyers used as the sample in this research. The technique of analyzing data used in this research were identification, classification and interpretation. The finding of this research shows the form of code mixing used by the sellers and buyers in Pasar Grosir Setono Pekalongan were from Javanese to Indonesian and Indonesian to Javanese. From those code mixing, there were the type of intra-sentential and intra-lexical used in their utterances. Based on the existing result, it is necessary to have language training in the field of marketing. It is used to improve the seller’s competence in speaking using Indonesian language and improve their confident to speak using Indonesian language. Keywords: Code mixing, conversation, bilingual